22nd AIAA Computational Fluid Dynamics Conference 2015
DOI: 10.2514/6.2015-3211
|View full text |Cite
|
Sign up to set email alerts
|

IDDES simulation of supersonic combustion using flamelet modeling

Abstract: A turbulent combustion modeling method combining the improved delayed detached eddy simulation (IDDES) model and the flamelet/progress variable (FPV) model is developed and then applied in the simulation of two supersonic combustors, namely the DLR supersonic combustor and the Gamba model combustor. Results show good agreement with the experiment, validating the accuracy of this method in supersonic combustion simulations. As a comparison, k-ω SST model combined with the FPV model is applied in the same cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…To the knowledge of the authors, when coming to the simulation of supersonic flows, in the published literature apart from Gieseking et al (2011) and Peterson and Candler (2011) IDDES always simply acts as a DDES approach (e.g., see Wang, Piao, & Niu, 2015), and even in the limited literature published where IDDES acts as WMLES the issue of underprediction of skin friction is rarely discussed (e.g., see Cocks, Bruno, Donohue, & Haas, 2013). No detailed assessment of IDDES acting as WMLES has ever been conducted regarding the prediction of mean skin friction in supersonic boundary layer flows.…”
Section: Introductionmentioning
confidence: 99%
“…To the knowledge of the authors, when coming to the simulation of supersonic flows, in the published literature apart from Gieseking et al (2011) and Peterson and Candler (2011) IDDES always simply acts as a DDES approach (e.g., see Wang, Piao, & Niu, 2015), and even in the limited literature published where IDDES acts as WMLES the issue of underprediction of skin friction is rarely discussed (e.g., see Cocks, Bruno, Donohue, & Haas, 2013). No detailed assessment of IDDES acting as WMLES has ever been conducted regarding the prediction of mean skin friction in supersonic boundary layer flows.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than tabulating all possible thermodynamic variables and transport properties (e.g., Saghafian et al [18] in the context of a compressible FPV model), we follow the approach suggested by Oevermann [32] and used by Wang et al [19]. That is, we tabulate the mass fractions obtained from the detailed chemistry WSR model and compute the local thermodynamic state from the density and energy computed by the CFD and the mass fractions interpolated from the table.…”
Section: Evm-les Implementationmentioning
confidence: 99%
“…Recent examples include compressible FPV simulations by Chan and Ihme [17], Saghafian et al [18], Wang et al [19], and Cao et al [20]; LEM simulations by Génin and Menon [21]; and TPDF and FMDF simulations by Delarue and Pope [22], Cocks et al [23], and Irannejad et al [24].…”
mentioning
confidence: 99%